Jaras Tambahan Yang “Tidak Biasa” - Yoga Yuniadi; Erika Maharani (Jurnal Kardiologi Indonesia, 2011)
Two cases of accessory pathway that were considered uncommon are presented. The first case shows of ECG limitation to identified manifest accessory pathway location based on delta wave morphology. The second case shows rare dual accessory pathways. Radiofrequency ablation has successfully eliminated all accessory pathway in both cases.